The Impact of Religion and Ideology on Country’s Economic Growth: A Case Study of Wukari Local Government Area, Taraba State - Wilson, Clement; N, Okeke E.; Akobi, Clement (Mikailalsys Journal of Mathematics and Statistics, 2025)
This study examines the influence of religion and ideology on economic growth in Wukari Local Government Area of Taraba State, Nigeria. Recognizing that religious beliefs and ideological values shape social cohesion, governance, and individual behavior, the research investigates how these factors contribute to local economic dynamics. A multi-stage cluster sampling technique was used to select ninety respondents across nine villages, representing Christianity, Islam, and African Traditional Religion. Data were collected through structured questionnaires and analyzed using descriptive statistics and multinomial logistic regression. The findings reveal that religious teachings and ideological orientations significantly shape economic behavior and perceptions of development. Specifically, religion promotes ethical values, work discipline, and social capital, generating both direct and indirect effects on economic growth. The regression model confirmed a statistically significant relationship between religious ideology and perceived economic advancement. However, the influence of religion can either facilitate or hinder economic progress, depending on how it is interpreted and applied. The study concludes that integrating religious values into economic planning in a balanced way can strengthen development outcomes. It recommends that policymakers and religious leaders foster inclusive, growth-oriented interpretations of faith and ideology to enhance sustainable economic development in the region.